Cellulose fatty acid ester coated papers for stand‐up pouch applications. Issue 48 (13th August 2018) - Willberg‐Keyriläinen, Pia; Ropponen, Jarmo; Alakomi, Hanna‐Leena; Vartiainen, Jari
ABSTRACT: Stand‐up pouches are one of the fastest growing packaging concepts, which are replacing the traditional packaging formats. In this study, stand‐up pouch prototypes are prepared from cellulose fatty acid coated heat‐sealed virgin kraft paper with leak proof seals. This study demonstrates that molar mass controlled cellulose ester (C6‐C16) coatings can significantly improve the barrier properties of virgin kraft paper. All cellulose ester coatings performed better compared to that of PLA. Cellulose ester coatings also improved the resistance of virgin kraft paper against tested nonpolar oil and grease compounds. In addition, the cellulose ester coatings had no antimicrobial activity, and fewer microbes adhered to them than to the PLA surface. The results demonstrate that cellulose fatty acid ester coatings have high potential in future applications requiring good barrier properties. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46936. Abstract :